Cryogels with controllable physico-chemical properties as advanced delivery systems for biomedical applications - Mucong Li; Xuyan Wei; Jiaqian You; Jian Feng; Xiuyu Liu; Jing Zhou; Qianju Wu; Yidi Zhang; Yanmin Zhou (Materials Today Bio)
Enhancing the spatiotemporal control of drug delivery holds significant potential for improving drug bioavailability, minimizing adverse reactions and toxicity, and advancing precision medicine. Traditional hydrogels have been widely recognized for their significance in substance delivery, attributed to their outstanding biocompatibility. Nevertheless, they exhibit certain limitations in the areas of controlled release and cell delivery. Cryogels, prepared using freezing technology, exhibit a unique macropores structure. The variations in technical parameters, such as the concentration of the gel precursor solution, freezing temperature, and freezing time facilitate adjustable mesh sizes and high pore connectivity. These characteristics are posited to enhance cell migration into the hydrogel interior and promote the transport of nutrients and metabolic waste. Their excellent toughness and injectability facilitate stress dispersion and provide effective cell protection. Consequently, cryogels modify drug release dynamics via their unique structure and integrate multiple release control mechanisms, thereby achieving spatiotemporal controlled delivery. This review paper provides an overview on synthesis methods, features, delivery advantages and mechanisms of cryogels. It further emphasizes the latest research advancements and applications of cryogels in spatiotemporal controlled delivery while acknowledging limitations associated with existing application methods.